Correlation between week 24 trastuzumab-dkst response and week 48 progression-free survival: the HERITAGE trial. (August 2021) - Rugo, Hope S.; Pennella, Eduardo J.; Gopalakrishnan, Unmesh; Hernandez-Bronchud, Miguel; Herson, Jay; Koch, Hans Friedrich; Loganathan, Subramanian; Deodhar, Sarika; Marwah, Ashwani; Manikhas, Alexey; Bondarenko, Igor; Parra, Joseph D.; et al.
Abstract: Background: Trastuzumab-dkst is a biosimilar of trastuzumab. The phase 3 HERITAGE trial demonstrated equivalent overall response rate (ORR) with trastuzumab-dkst or originator trastuzumab at 24 weeks in patients with HER2-positive metastatic breast cancer receiving chemotherapy. We now present the correlation of ORR with progression-free survival (PFS) for maintenance monotherapy with trastuzumab-dkst vs trastuzumab at 48 weeks of treatment, and the safety, tolerability, and immunogenicity. Methods: HERITAGE is a multicenter, double-blind, randomized, parallel-group, phase 3 study. Patients were randomized 1:1 to receive trastuzumab-dkst or trastuzumab in combination with taxane followed by continued monotherapy until disease progression. The analysis included PFS at 48 weeks to support the primary efficacy endpoint of ORR and safety, tolerability, and immunogenicity of trastuzumab-dkst vs trastuzumab as maintenance monotherapy. Results: Of 500 randomized patients, 342 entered the monotherapy phase; 214 patients received ≥48 weeks of treatment. There were no statistically significant differences between PFS, ORR, or interim overall survival at week 48 between trastuzumab-dkst and trastuzumab. Week 24 ORR was highly correlated with week 48 PFS (rb  = 0.75). Cumulative treatment-emergent adverse events (TEAEs) and serious AEs were similar in both groups, with few grade ≥3 TEAEs. Immunogenicity was low and similar in both groups at 48 weeks. Conclusion: The correlation between ORR and PFS supports the design of first-line metastatic trials assessing biosimilar trastuzumab. Overall, trastuzumab-dkst and trastuzumab were well tolerated with similar efficacy, including ORR and PFS, in combination with a taxane followed by monotherapy. Highlights: Trastuzumab-dkst is a biosimilar of trastuzumab. Trastuzumab-dkst and trastuzumab had similar PFS, ORR, and OS at week 48. Results support therapeutic equivalence between trastuzumab-dkst and trastuzumab. Week 24 ORR was highly correlated with week 48 PFS. ORR and PFS correlation supports ORR as a valid endpoint in clinical trials for MBC.